Transurethral anatomical enucleation of the prostate with Tm:YAG support (ThuLEP): Evolution and variations of the technique. The inventors' perspective. (14th April 2020) - Herrmann, Thomas R. W.; Wolters, Mathias
Abstract: After its introduction, transurethral anatomical enucleation of the prostate with Tm:YAG support (ThuLEP) has evolved as one of the standard techniques of transurethral anatomical endoscopic enucleations of the prostate. Growing evidence has proven ThuLEP as an alternative for the treatment of bladder outlet obstruction caused by benign prostatic enlargement and has been acknowledged by the EAU Guidelines on Management of Non‐Neurogenic Male Lower Urinary Tract Symptoms, incl. Benign Prostatic Obstruction. The uniqueness of ThuLEP as a concept made it a blueprint for other laser and nonlaser enucleating techniques based on the emphasis on two principles: widely blunt anatomical dissection and demystification of energy sources as being secondary for transurethral enucleation. The original technique has been technically refined by the inventor and other working groups in the field. The evolutionary modifications followed the academic discourse on anatomical enucleation for measures to prevent early postoperative stress urinary incontinence and preservation of antegrade ejaculation. Variations of the original three‐lobe dissection technique were introduced with two‐lobe approach or en bloc dissection. The manuscript is accompanied by an instructional video and surgical atlas on the currently most commonly applied two‐lobe technique.